2014
DOI: 10.15403/jgld.2014.1121.233.vpb2
|View full text |Cite
|
Sign up to set email alerts
|

Giant Solitary Gastric Peutz-Jeghers Polyp Mimicking a Malignant Gastric Tumor: the Largest Described in Literature

Abstract: A solitary Peutz-Jeghers polyp is defined as a unique polyp occurring without associated mucocutaneous pigmentation or a family history of Peutz-Jeghers syndrome. Gastric solitary localization is a rare event, with only eight reported cases to date. We report herein the case of a 43-year old woman who presented with upper gastrointestinal bleeding, severe anemia, weight loss and asthenia. Endoscopy revealed a giant polypoid tumor with signs of neoplastic invasion of the cardia, with pathological aspect suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Moderate dysplasia may be diagnosed [ 8 ], because the fragile superficial area is prone to inflammatory erosion. Two patients had swollen lymph nodes [ 8 , 9 ] that were finally diagnosed as reactive hyperplasia without tumor metastasis. Reactive lymph-node swelling is probably due to inflammatory changes on the surfaces of polyps.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate dysplasia may be diagnosed [ 8 ], because the fragile superficial area is prone to inflammatory erosion. Two patients had swollen lymph nodes [ 8 , 9 ] that were finally diagnosed as reactive hyperplasia without tumor metastasis. Reactive lymph-node swelling is probably due to inflammatory changes on the surfaces of polyps.…”
Section: Discussionmentioning
confidence: 99%
“…The solitary gastric Peutz–Jeghers-type polyps are the rarest. [ 6 ] Kuwano et al [ 7 ] reported a case of solitary gastric hamartomatous polyp in 1989 for the first time. So far, only 9 cases of the solitary gastric Peutz–Jeghers-type polyp were reported abroad (Table 1 ), and a few cases were reported in China, some of which were not adequately detailed.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] A few cases are similar to the tumor, even with similar performance of tumor metastasis such as enlarged lymph nodes. [ 6 , 9 ] Therefore, the doctor must be very careful during diagnosis. The diagnosis of solitary Peutz–Jeghers-type polyps should be based on pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the existence of this pathological entity is of great importance since it can emulate clinically and histologically a malignant lesion of the colon, leading to unnecessary operative management [ 1 , 6 , 8 ]. Solitary Peutz-Jeghers-type polyp is an uncommon hamartomatous lesion without associated mucocutaneous pigmentation, any other gastrointestinal polyp or a family history of Peutz-Jeghers syndrome [ 9 – 11 ]. To the best of our insight, its association with CCP and dysplastic changes in the overlying epithelium has never been reported again in the English scientific writings.…”
Section: Introductionmentioning
confidence: 99%